POTENSI PENGGUNAAN OBAT TIDAK TEPAT PADA PASIEN RAWAT JALAN GERIATRI BERDASARKAN KRITERIA BEERS 2019 - Rahmawati, Reza; Harianti Putri, Yona; Handayani, Dian; Pertiwi, Reza; Putri Nurlita, Septia; Kamilla Putri, Dwi; Alawiya Simanullang, Khairatul (Jurnal Kefarmasian Akfarindo, 2022)
Geriatric population continues to increased globally. In Indonesia, estimation of geriatric population is 7% and will be increase over years. One of geriatric medication problem is potentially inappropriate medication (PIM). Beers criteria 2019 is one of a tool to evaluate potentially inappropriate medication in geriatric. Therefore, this study aims to indentify the prevalence of potentially inappropriate medication incidence in geriatric outpatient at Pharmacy X in Bengkulu and risk factors associated with PIM. This research was done in cross sectional and prospective study. Data collection was done in 2 months from August-October 2021. The incidence of potentially inappropriate medication was analyzed using descriptive analysis according to Beers Criteria 2019 and risk factors were analyzed using logistic regression. This research reported that from 115 geriatric patients above ≥ 65 years old, out of 56 patients (48,70%) found with at least 1 potentially inappropriate medication (PIM). There were 101 PIM with average of PIM 1,8 PIM/patient. Drug should be avoid in almost geriatrics were 34,65%, drug used with caution in geriatrics were 54,46%, and drug interaction should be avoid in geriatric were 10,89%. Diuretic agents like furosemide and spironolactone were frequently used in geriatric patients but potentially inappropriate. Logistic regression showed that the number of drugs used is associated with the incidence of PIM in geriatric outpatient.